Interaction of TMPyP4, TMPyP3, and TMPyP2 with Intramolecular G-Quadruplex Formed by Promoter Region of Bcl2 and KRAS NHPPE. (7th February 2012) - Nagesh, Narayana; Ganesh Kumar, Arumugam
Abstract : Oncogenes are rich in guanine and capable of forming quadruplex structure. Promoter regions oncogenes such as Bcl2 and KRAS NHPPE are rich in guanine content and they can form quadruplex structures. Alterations in the mode and nature of molecular binding to DNA, certainly has effect on the posttranscriptional activities. Recent experiments indicate that structure of quadruplex complex and ligand has predominant role on ligand-quadruplex DNA interaction. In order to understand the nature of each ligand interaction with quadruplex DNA, Bcl2, KRAS NHPPE quadruplex DNA interaction with three porphyrin was studied using spectroscopy, microcalorimetry and mass spectrometry. Our studies, indicate that mode of ligand interaction varies with structure, environment and concentration of ligand. Fluorescence quenching experiments show that TMPyP4 interaction is ligand concentration dependent. Job plots and ITC experiments demonstrate that four molecules of TMPyP4 and two molecules of TMPyP3, TMPyP2 interact with each quadruplex complex. Through ITC titrations, ligand binding constant are higher for TMPyP4 ( ≈ 10 7  M −1 ) compared to TMPyP3, TMPyP2 ( ≈ 10 5  M −1 ). ESI-MS experiments confirm the stoichiometry of TMPyP4 : 39Bcl2 is 4 : 1 at saturation and it is 2 : 1 in case of KRAS NHPPE quadruplex.